Toward an African Church in Mozambique: Kamba Simango and the Protestant Communtity in Manica and Sofala - Spencer, Leon P. (African Books Collective, 2013)
Literature about Christianity in Africa disproportionately directs attention to the important work of Western missionaries, but to a great extent Africans were the agents of their own conversion. This is true of the key figure in this book, Kamba Simango. Encouraged from a distance by an American Congregationalist missionary, Fred R. Bunker, who shared his commitment to an African-led work, Simango, Tapera Nkomo and others struggled against difficult odds in the Mozambique Company region of Manica and Sofala in Central Mozambique. This study reveals the humanity of its characters as well as th